Evaluating International Ethical Climates: A Goal Programming Model - Hoffman, James J. (Journal of business ethics, 1998)
A critical concern for firms pursuing international expansion strategies involves identifying countries that offer a good fit with the firm's overall ethical orientation. Unfortunately, little has been written to aid firms in identifying countries that offer this type of fit. This paper presents a model that combines the concepts of strategic management, cross-cultural management, business ethics, and the management science technique of goal programming. The purpose of the model is to aid managers in identifying countries for international expansion that offer the best fit with the firm's ethical orientation. The paper also extends the existing literature on cross-cultural management and business ethics by applying a computer optimization model to evaluate potential countries for international expansion in a way that has not been done before.